2009
DOI: 10.1007/s12297-009-0055-9
|View full text |Cite
|
Sign up to set email alerts
|

Hedge-Fonds als Asset-Klasse: Betrachtungen aus der Perspektive der deutschen Versicherungswirtschaft

Abstract: Zusammenfassung Die bis kurz vor der Krise so renditestarken Hedge-Fonds haben viele Versicherer dazu gebracht, den Hedge-Fonds-Anteil an ihrem Portfolio aufzustocken. Im Folgenden soll diese Assetklasse untersucht und insbesondere geprüft werden, ob sie dem Grundsatz der Sicherheit, wie er explizit gefordert wird, genügt. Es werden dabei die Probleme des Survivorship-Bias, der Normalverteilungsannahme und der instabilen Korrelationen genauer betrachtet, da diese im Rahmen einer Markowitz-Optimierung zu massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Most importantly, we have shown that a major macroeconomic crisis can also have additional -and more microeconomic -effects on the relationship between financial assets that have been thought to be quite similar. More specifically, Reddemann et al (2009) have argued that structural breaks in linear regressions of the type displayed in equation (1) can be a sign of instability and time variation of the correlations between the returns of the asset classes examined. Therefore, the empirical evidence reported above is also a reminder of the fact that the correlation matrices of returns on different financial assets regularly used in financial optimizations are not necessarily stable over time.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, we have shown that a major macroeconomic crisis can also have additional -and more microeconomic -effects on the relationship between financial assets that have been thought to be quite similar. More specifically, Reddemann et al (2009) have argued that structural breaks in linear regressions of the type displayed in equation (1) can be a sign of instability and time variation of the correlations between the returns of the asset classes examined. Therefore, the empirical evidence reported above is also a reminder of the fact that the correlation matrices of returns on different financial assets regularly used in financial optimizations are not necessarily stable over time.…”
Section: Resultsmentioning
confidence: 99%